2014
DOI: 10.3174/ajnr.a3925
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Flow-Diverting Device (Tubridge) for the Treatment of 28 Large or Giant Intracranial Aneurysms: A Single-Center Experience

Abstract: BACKGROUND AND PURPOSE:The Tubridge flow diverter is a novel device developed in China and aimed at reconstructing the parent artery and occluding the aneurysm. We conducted this study to evaluate its feasibility, safety, and efficacy for the treatment of large or giant internal carotid artery aneurysms, which are still challenging with conventional therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…The technical success rate, clinical outcome, and angiographic results are in line with the findings of comparable series. 1,[3][4][5][11][12][13] The device itself is being developed further, similar to modifications to the PED and NeuroEndoGraft.…”
Section: Discussionmentioning
confidence: 99%
“…The technical success rate, clinical outcome, and angiographic results are in line with the findings of comparable series. 1,[3][4][5][11][12][13] The device itself is being developed further, similar to modifications to the PED and NeuroEndoGraft.…”
Section: Discussionmentioning
confidence: 99%
“…Tubridge flow diverters harbor a pore size of 0.040–0.050 mm 2 at the nominal diameter to provide high metal coverage (approximately 30.0–35.0%) at the aneurysmal neck after expansion. A complete occlusion rate for anterior circulation aneurysms treated with Tubridge stents after an average of 19.0 months of follow-up was 72%,8 and that for posterior circulation aneurysms at a median of 26.0 months of follow-up 83% 9…”
Section: Discussionmentioning
confidence: 97%
“…[7] Preliminary evidence has demonstrated their safety and efficacy for treating complex aneurysms. [6] The Tubridge FD is a stent-like vessel-reconstruction devise designed with a high metal coverage rate and low porosity and was approved by the Ethics Committee of our institution and by the Chinese Lvis, and have shown that simulation can be useful during stent deployment. [12] Ospel et al supposed that simulated length of Pipeline calculated by software was shorter than the manually determined presumed optimal devices.…”
Section: Discussionmentioning
confidence: 99%